Aspects of holography - Findeis, Dirk Michael; Findeis, Dirk Michael (Department of Mechanical Engineering, 2017)
This study was aimed at broadening the knowledge of aspects of holography by examining three areas of importance, namely: i) qualitative holographic nondestructive testing, as applicable to flaw detection, ii) quantitative holographic interferometry and iii) white-light transfer reflection holography, with particular emphasis on the multiplexing principle. The objects used to evaluate the viability of qualitative holographic nondestructive testing were various carbon fibre airframe sections, a ceramic tube and a ceramic mould. The real-time and double-exposure holographic techniques were used to investigate the objects. Hot air was employed as the stress application medium. The results obtained clearly show the viability of holography as a nondestructive testing technique for the detection of debonds, delaminations, cracks, etcetera. In the second part of the study, the zero-order and fringe-counting techniques were applied to a cantilever loading experiment as a means of quantitatively determining the cantilever's displacement. It was determined that displacements with an accuracy of circa 85 % could be obtained by using the abovementioned techniques. In the final part of this study the transfer and multiplexing principles were rigorously examined. As a result, it was found that when reflection holograms were used as masters, excessively dim transfer holograms were produced. Transmission masters produced much brighter transfer holograms and displayed the capability of individually reproducing the images recorded. However, the angle of visibility of the individual images produced was found to be unsatisfactory and therefore warrants further investigation.